Equity versus Inequity in the Different Autonomous Laws of Dignified Death in Spain (Revista Iberoamericana de Bioética, 2020)
In Spain, ten regional Autonomous Communities legally regulate the right to die with dignity. The aim here is to analyze whether those laws allow for fair decisionmaking and equivalent quality of assistance. The method used was a documentary qualitative study based on comparative analysis of regional laws. The results show a homogeneity of assistance rights but differences in the conceptualization and conditions of application of the limitation of therapeutic effort (LTE) or the adaptation of therapeutic effort (ATE). The conclusion reached is that a lack of equal criteria on LTE and ATE are conditions of a different assistance according to territories.
Keywords: health equity; palliative care; death; patient rights